Prevalence of Antiretroviral Drug Resistance Mutations and HIV-1 Subtypes among Newly-diagnosed Drugnaïve Persons Visiting A Voluntary Testing and Counselling Centre in Northeastern South Africa (Journal of Health, Population and Nutrition, 2011)
Data on antiretroviral drug resistance among drug-naive persons are important in developing sentinel and surveillance policies. This study was conducted to determine the prevalence of antiretroviral drug resistance mutations among drug-naive HIV-infected individuals attending a voluntary testing and counselling centre at the Mankweng Hospital in northeastern South Africa. In total, 79 drug-naive HIV-positive individuals were sequentially recruited during February 2008–December 2008. Drug resistance mutations were determined using the calibrated population resistance tool available on the Stanford HIV drug resistance database. Viral DNA was obtained from 57 (72%) of the 79 individuals. Reliable nucleotide sequences were obtained for 54 reverse transcriptase (RT) and 54 protease (PR) gene regions from 54 individuals. Overall, five sequences (9.3%) harboured drug resistance mutations (95% confidence interval -1.53 to 16.99). Four (7.4%) of these were nucleoside RT inhibitor mutations (D67G, D67E, T69D, and T215Y), and one (1.9%) was a PR inhibitor mutation (M46I). No major non-nucleoside RT resistance mutation was detected. Several minor resistance mutations and polymorphisms common in subtype C viruses were observed in the PR and RT genes. Phlyogenetic analysis of the partial pol sequences showed that 52 (96%) of the 54 isolates were HIV-1 subtype C. One isolate (08MB08ZA) was HIV-1 subtype B while another (08MB26ZA) was related to HIV-1 subtype J. HIV-1 subtype recombination analysis with REGA assigned the pol sequence to HIV subtype J (11_cpx) with a bootstrap value of 75%. The prevalence of drug resistance mutations observed in the population studied was relatively higher than previously reported from other parts of South Africa. In addition, this is apparently the first report of an HIV-1 subtype J-like virus from northeastern South Africa. Key words: Antiretrovirals; Drug resistance; Drug-naive persons; HIV-1; South Africa DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8444 JHPN 2011; 29(4): 303-309